A "Double-Locked" and enzyme-activated molecular probe for accurate bioimaging and hepatopathy differentiation. Issue 47 (22nd October 2019) - Liu, Yongchao; Teng, Lili; Xu, Chengyan; Liu, Hong-Wen; Xu, Shuai; Guo, Haowei; Yuan, Lin; Zhang, Xiao-Bing
Abstract : A "double-locked" and enzyme-activated molecular fluorescent probe for accurate bioimaging and hepatopathy differentiation. Abstract : Molecular probes activated by a single enzyme have been extensively used in bioimaging and disease diagnosis; however, imaging and identification in an accurate manner remains a challenge for such probes. Here, based on the specificity of enzyme recognition, we engineered a "double-locked" and enzyme-activated molecular probe (NML ) for accurate bioimaging and hepatopathy differentiation. Triggered by the successive reactions with leucine aminopeptidase (LAP, first "key") and monoamine oxidase (MAO, second "key"), the emissive fluorophore (NF ) was released. NML can be activated only in the presence of both LAP and MAO and can be silenced when either enzyme is inhibited. Benefiting from the "double-locked" strategy, NML showed higher accuracy for imaging of drug-induced liver injury (DILI) than the "single-locked" probe. With serum testing, NML showed significant differences in mouse models of both CCl4 -induced liver cirrhosis and DILI. Significantly, NML can be applied to accurately distinguish serum samples from clinical patients with different hepatopathies. Our smart molecular probe may hold great potential for hepatopathy diagnosis and clinical transformation.